The HUman MicroNucleus project on eXfoLiated buccal cells (HUMNXL): The role of life-style, host factors, occupational exposures, health status, and assay protocol - Bonassi, Stefano; Coskun, Erdem; Ceppi, Marcello; Lando, Cecilia; Bolognesi, Claudia; Burgaz, Sema; Holland, Nina; Kirsh-Volders, Micheline; Knasmueller, Siegfried; Zeiger, Errol; Carnesoltas, Deyanira; Cavallo, Delia; et al. (Elsevier B.V., 2011)
The human buccal micronucleus cytome assay (BMCyt) is one of the most widely used techniques to measure genetic damage in human population studies. Reducing protocol variability, assessing the role of confounders, and estimating a range of reference values are research priorities that will be addressed by the HUMNXL, collaborative study. The HUMNXL, project evaluates the impact of host factors, occupation, life-style, disease status, and protocol features on the occurrence of MN in exfoliated buccal cells. In addition, the study will provide a range of reference values for all cytome endpoints. A database of 5424 subjects with buccal MN values obtained from 30 laboratories worldwide was compiled and analyzed to investigate the influence of several conditions affecting MN frequency. Random effects models were mostly used to investigate MN predictors. The estimated spontaneous MN frequency was 0.74 parts per thousand (95% CI 0.52-1.05). Only staining among technical features influenced MN frequency, with an abnormal increase for non-DNA-specific stains. No effect of gender was evident, while the trend for age was highly significant (p < 0.001). Most occupational exposures and a diagnosis of cancer significantly increased MN and other endpoints frequencies. MN frequency increased in heavy smoking (>= 40 cig/day. FR = 1.37:95% CI 1.03-.82) and decreased with daily fruit consumption (FR = 0.68; 95% CI 0.50-0.91). The results of the HUMNXL, project identified priorities for validation studies, increased the basic knowledge of the assay, and contributed to the creation of a laboratory network which in perspective may allow the evaluation of disease risk associated with MN frequency. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Buccal micronucleus cytome assay (BMCyt); Genetic instability; Exfoliated cell; Pooled analysis; Molecular epidemiology; Assay standardization